Weight loss is associated with sustained improvement of disease activity and cardiovascular risk factors in patients with psoriatic arthritis and obesity: a prospective intervention study with two years of follow-up - Klingberg, Eva (Arthritis Res Ther, 2020)
BACKGROUND: Obesity is overrepresented in patients with psoriatic arthritis (PsA) and associated with increased disease activity. We have previously shown in 41 patients with PsA (Caspar criteria) and obesity (body mass index; BMI ≥33 kg/m(2)) that weight loss treatment with Very Low Energy Liquid Diet (VLED), 640 kcal/day during 12–16 weeks, followed by a structured reintroduction of an energy restricted diet resulted in a median weight loss of 18.6% and concomitantly a significant improvement of the disease activity in joints, entheses and skin. The objectives of this follow-up were to study the effects of the weight loss treatment on disease activity in longer term (12 and 24 months) and to study the effects on cardiovascular risk factors. METHODS: The patients were assessed with 66/68 joints count, Leeds enthesitis index (LEI), body surface area, blood pressure, BMI, questionnaires and fasting blood samples at the 12- and 24-month visits. RESULTS: In total, 39 and 35 PsA patients attended the 12- and the 24-month visits, respectively. Median weight loss since baseline was 16.0% (IQR 10.5–22.4) and 7.4% (IQR 5.1–14.0) at the 12- and 24-months follow-up. The 66/68 swollen/tender joints score, LEI, CRP and HAQ score were still significantly reduced at the 12- and 24-month visits compared to baseline. The number of patients with Minimal Disease Activity increased from 28.2% (11/39) at baseline, to 38.5% (15/39; p = 0.008) and 45.7% (16/35; p = 0.016) at the 12- and 24-month visits. The weight loss was also associated with improved levels of serum lipids, glucose and urate and the antihypertensive treatment was reduced or stopped in five patients during the follow-up. CONCLUSIONS: Weight loss treatment, with VLED included in the program, was associated with long-term improvement of measures of disease activity, self-reported function and markers of the metabolic syndrome after 24-months follow-up. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02917434, Registered September 28, 2016- Retrospectively registered.